Perturbações bariônicas num modelo com decaimento do vácuo - Marttens, Rodrigo Fernando Lugon Cornejo vom (2013)
According to our understanding of the universe dark matter and dark energy are the dominant components in the dynamics of the present universe, while the baryons and radiation contribute only a small fraction less than 5% of cosmic energy. On the other hand, the study of the observed inhomogeneities in the matter distribution requires knowledge of the dynamics of this baryonic fraction, since it is the distribution of this fraction which is directly observed. It is not clear that the baryonic matter inhomogeneities coincide with the inhomogeneities of dark matter. In particular, if the dark matter interacts nogravitationally with dark energy while the baryonic matter motion is geodesic, this issue should be clarified. In this work we incorporate into a decaying vacuum model a separately conserved baryon fluid, whose fourvelocity, on the perturbative level, differs from fourvelocity dark matter. The inclusion of baryons does not seem to affect the homogeneous and isotropic background, but on the perturbative level it seems to reduce the contribution of matter to the total energy budget